DERIVATIONAL MORPHEMES ANALYSIS OF CATEGORIES AND FUNCTIONS IN JEFF BEZOS’ TWEETS: MORPHOLOGICAL APPROACH. - Wel Son; Delia Anyelir; Afriana Afriana (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
The aim of this research is to analyze the derivational morphemes categories and the additional meaning of the words by the addition of the morphemes in Jeff Bezos’ tweets. Jeff Bezos, as an entrepreneur and economic influencer was found using dictions of words containing derivational morphemes in his tweets. Therefore, the morphological analysis is important in order to know the role of morphemes in obtaining the intended meaning. The researchers used the theory from Fromkin et al. (2017) to analyze the categories and Sheehan (2000) to analyze the additional meaning of the words based on the addition of morphemes. Descriptive qualitative method was taken in order to analyze the data, and the data was collected by using observational method which then reduced from the tweets of 2018 to 2022. As the results of the research, 85 morphemes were found that change the parts of speech of the words, including 13 suffixes that changed noun to adjective, 35 suffixes that changed verb to noun, 15 suffixes that changed adjective to adverb, 2 suffixes and 1 prefix that changed noun to verb, 11 suffixes that changed adjective to noun, and 8 suffixes that changed verb to adjective. Moreover, the researcher also found 7 suffixes and 16 prefixes that did not change the part of speech of the words. Furthermore, it was also found that the morphemes brought a significance in giving the additional meaning for the words.